Citraan dan Majas dalam Lirik Lagu "Harehare Ya" Karya Maigo Hanyuu Kajian Stilistika - Nur Hastuti; Sri Rezeki Ayuni (IZUMI, 2023)
Song lyrics are part of the music. Music is made up of rhythm, time signature, harmony and melody. Song lyrics act as one of the elements in the main melody in a music. This study aims to describe the images and figure of speech in the lyrics of the song harehare ya by Maigo Hanyuu. The method used in this study uses stylistic studies as an analytical tool. The data used in this study are the lyrics of the song harehare ya by Maigo Hanyuu. The theory used is Hermintoyo's imagery theory and Seto Kenichi's figure of speech theory. Based on data analysis, it can be concluded that in the lyrics of the song harehare ya by Maigo Hanyuu, imagery and figurative language are found. There are four imagery in the lyrics of this song, namely, imagery of sight, hearing, movement, and feeling. In the lyrics of this song, there are also many figurative language of affirmation dominated by repetition. There are nine repetition figures of speech in the lyrics of this song, and rhetorical figures of speech in the lyrics of this song are two. Keywords: Figure of speech,  harehare ya, imagery,  song lyrics gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor